Adhesion molecules in rheumatoid arthritis: role in the pathogenesis and prospects for therapy. Issue 5 (May 1994) - Pitzalis, C; Kingsley, G; Panayi, G
Abstract : The essential role played by cell adhesion and migration in the generation of chronic synovitis is now beyond doubt. Some of the beneficial effects of currently used drugs may be related to their ability to interfere with these mechanisms. The complexity of the process, however, means that there are many potential targets for therapeutic intervention and therefore further studies of the basic mechanisms are necessary to identify those which are most important.